3D Bioprinting in Plant Science: An Interdisciplinary Approach. (January 2020) - Mehrotra, Shakti; Kumar, Smita; Srivastava, Vikas; Mishra, Taijshee; Mishra, Bhartendu Nath
Abstract : Here we highlight advances and opportunities for using 3D bioprinting in plant biology research that could lead to low-cost solutions for biomedical and other applications. For example, the development of plant cell-based and plant-inspired 3D-printed constructs could provide information about single-cell, tissue, and whole-plant interactions with the surrounding environment.